Social Support and Depressive Symptoms: The Mediating Role of Self-Esteem - Melkorka Sól Sigurjónsdóttir 1999- (2023)
Social support is one of many social behaviors that are an important part of human lives. This support can be received from anyone in an individuals’ social environment, but the most important provider of social support is the family. The aim of this study was to examine the relationship between perceived social support from family and depressive symptoms among university students. In addition, the aim was to explore the mediating effects that self-esteem could have on that connection. In 2023, a survey was sent to all students at the Reykjavík University and 470 valid responses were gathered. Using Pearson's correlation, the results showed that both social support from family and self-esteem had negative correlations with depressive symptoms. This indicates that with higher perceived social support from family or higher self-esteem, university students experienced less depressive symptoms. Additionally, mediation analysis displayed that self-esteem partially mediated the relationship between perceived social support from family and depressive symptoms, meaning that the impact that social support from family had on depressive symptoms was partly explained by self-esteem. These results deepen the understanding of the importance of social support from family and self-esteem on mental health of university students. Keywords: Social support, depressive symptoms, self-esteem, mental health, university students Félagslegur stuðningur er ein af mörgum félagslegum hegðunum sem eru hluti af lífi fólks. Þessi stuðningur getur komið frá hverjum sem er í félagslegu umhverfi einstaklingsins, en mikilvægasta uppspretta stuðningsins er fjölskyldan. Markmið þessarar rannsóknar var að skoða tengsl milli félagslegs stuðnings frá fjölskyldu og einkenna þunglyndis meðal háskólanema. Einnig var markmiðið, að skoða möguleg miðlunaráhrif af sjálfstrausti á þetta samband. Árið 2023 var könnun var send á alla nemendur Háskólans í Reykjavík og bárust 470 gild svör. Pearson’s fylgni prófun sýndi að bæði félagslegur stuðningur frá ...